2014
DOI: 10.1093/pasj/psu052
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of molecules in the circumnuclear disk and surrounding starburst ring in the Seyfert galaxy NGC 1068 observed with ALMA

Abstract: Sensitive observations with the Atacama Large Millimeter/submillimeter Array (ALMA) allow astronomers to observe and discuss the detailed distributions of molecules with relatively weak intensity in nearby galaxies. In particular, we report distributions of several molecular transitions including shock and dust related species ( 13 CO J = 1-0, C 18 O J = 1-0, 13 CN N = 1-0, CS J = 2-1, SO J N = 3 2 -2 1 , HNCO J Ka,Kc = 5 0,5 -4 0,4 , HC 3 N J = 11-10, 12-11, CH 3 OH J K = 2 K -1 K , and CH 3 CN J K = 6 K -5 K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 67 publications
(113 reference statements)
9
57
1
Order By: Relevance
“…This is an indication of a significant asymmetrical distribution of the molecular gas in the CND (also seen in CO 2−1, Hsieh et al 2008), similar to what is observed at higher resolution in NGC 1068 . Also in NGC 1068, though at slightly lower resolution, the emission of HNCO is observed distributed in two lobes at both sides of the AGN (Takano et al 2014). Such double peak distribution is in agreement with the CND being observed from a more inclined direction consistent with its Seyfert 2 nucleus.…”
Section: The Cnd Traced By Hncosupporting
confidence: 82%
See 4 more Smart Citations
“…This is an indication of a significant asymmetrical distribution of the molecular gas in the CND (also seen in CO 2−1, Hsieh et al 2008), similar to what is observed at higher resolution in NGC 1068 . Also in NGC 1068, though at slightly lower resolution, the emission of HNCO is observed distributed in two lobes at both sides of the AGN (Takano et al 2014). Such double peak distribution is in agreement with the CND being observed from a more inclined direction consistent with its Seyfert 2 nucleus.…”
Section: The Cnd Traced By Hncosupporting
confidence: 82%
“…The densest gas: SiO, HNCO and HC 3 N These three species are the ones showing the clearest contrast between the central region and the SF ring with a significant enhancement toward the nuclear region. Toward NGC 1068, an enhancement of SiO and HC 3 N in the surroundings of the AGN was already been recently reported (García-Burillo et al 2010;Takano et al 2014).…”
Section: Star Formation: Cchmentioning
confidence: 81%
See 3 more Smart Citations